Implementation of Collage Techniques to Improve Cognitive and Fine Motor Skills in Children Aged 4-6 Years - Lily, Netry Maria; Tabun, Norlianti L; Maarang, Matrheda (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Early childhood development is an essential period for establishing the groundwork and gaining abilities that will impact a child's life ahead. A child's growth is influenced by the stimulation they experience; when they receive adequate stimulation in their early years, children will mature and develop suitably for their age. Some of the essential areas of growth include cognitive abilities and fine motor skills. An engaging educational task that promotes both cognitive skills and fine motor abilities is creating collages. Collage consists of crafting art by adhering dry leaves or various materials to a flat surface or drawing with glue. This service seeks to present new strategies for children, promote imaginative learning techniques, and enhance the growth of cognitive and fine motor skills to guarantee healthy development. The service involved 30 children between the ages of 4 and 6 through techniques like parent socialization, training, and mentoring for children. The technique of creating collages was especially effective for improving cognitive and fine motor skills, as it allows children to enhance their problem-solving skills and reinforces their small muscle development.